Front Cover: Operando Electron Microscopy Study of Cobalt‐based Fischer‐Tropsch Nanocatalysts (ChemCatChem 8/2021). Issue 8 (31st March 2021) - Dembélé, Kassiogé; Bahri, Mounib; Hirlimann, Charles; Moldovan, Simona; Berliet, Adrien; Maury, Sylvie; Gay, Anne‐Sophie; Ersen, Ovidiu
Abstract : The Front Cover displays a microscopic view of the physico‐chemical processes and molecular compounds involved in the Fischer‐Tropsch synthesis. In their Full Paper, K. Dembélé et al. report on the direct monitoring of the behavior of cobalt‐based nanocatalysts during the reduction step and the following catalytic reaction, by coupling in situ transmission electron microscopy and mass spectrometry and combining additional techniques and catalytic tests. This multiselective approach allows to directly correlate the evolution of the catalytic behavior of the nanoparticles to their structural transformations via processes such as particle fragmentation, migration and coalescence. Our results underline the benefit of using operando microscopy techniques to study the dynamical evolution of catalysts, at the nanoparticle level, under operation conditions. More information can be found in the Full Paper by K. Dembélé et al.